2005
DOI: 10.2466/pr0.96.1.122-128
|View full text |Cite
|
Sign up to set email alerts
|

Foot-in-the-Door and Door-in-the-Face: A Comparative Meta-Analytic Study

Abstract: The so-called foot-in-the-door and door-in-the-face techniques have been generally considered as procedures which may consistently influence others' behavior. This study compared efficiency (in terms of compliance rates with various target requests) of both techniques using meta-analysis. It is based on the accumulated studies directly comparing foot-in-the-door (n=22, subjects= 1581) and door-in-the-face (n=22, subjects= 1611) under a similar target request. Analysis indicated no significant differences in ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 37 publications
2
42
0
2
Order By: Relevance
“…This effect is also commonplace in social psychological literature. In particular, research on the foot-in-the-door phenomenon suggests that people are likely to endorse a larger request or comply with a regulation, once they have been induced to accept a smaller preceding and relevant demand (Pascual and Guegen 2005;Rodafinos et al 2005). Along these lines, the present findings suggest that policies against youth smoking (e.g., prohibiting cigarette sales to minors) may spearhead attempts to bolster positive attitudes to tobacco control policies in both smokers and non-smokers.…”
Section: Discussionmentioning
confidence: 61%
“…This effect is also commonplace in social psychological literature. In particular, research on the foot-in-the-door phenomenon suggests that people are likely to endorse a larger request or comply with a regulation, once they have been induced to accept a smaller preceding and relevant demand (Pascual and Guegen 2005;Rodafinos et al 2005). Along these lines, the present findings suggest that policies against youth smoking (e.g., prohibiting cigarette sales to minors) may spearhead attempts to bolster positive attitudes to tobacco control policies in both smokers and non-smokers.…”
Section: Discussionmentioning
confidence: 61%
“…For solicitors, presenting a few coins in their hand when asking unknown passersby for money increased the probability of receiving money in return. The weighted mean correlation coefficient for the three studies appeared moderate (M ¼ .31) but also more important than results found with other compliance techniques such as the foot-in-the-door technique (r < .10: Beaman, Cole, Preston, Klentz, & Steblay, 1983;Burger, 1999;Dillard, Hunter, & Burgoon, 1984;Fern, Monroe, & Avila, 1986;Pascual & Guéguen, 2005), the door-in-the-face technique (r < .13: Dillard et al, 1984;Feeley, Anker, & Aloe, 2012), the "but your are free of . .…”
Section: Discussionmentioning
confidence: 73%
“…The FITD technique is viewed by many social psychologists as a highly versatile strategy that has been used to gain compliance in many situations, including increasing donations to charities (Guéguen & Jacob, 2001), completing mail-in surveys (Cialdini, Trost, & Newsom, 1995), increasing volunteerism (Guadagno, Asher, Demaine, & Cialdini, 2001), and agreeing to become an organ donor (Carducci, Deuser, Bauer, Large, & Ramaekers 1989). Nearly five decades of research and over 100 studies revealed that the FITD technique is reliable in gaining compliance (Beaman, Cole, Preston, Klentz, & Steblay, 1983;Burger 1999;Dillard, Hunter, & MR. BIG TECHNIQUE 11 Burgoon, 1984;Fern, Monroe, & Avila, 1986;Pascual & Guéguen, 2005). Within a Mr. Big operation, the target becomes committed to the organization by agreeing to complete very small jobs initially, such as transporting goods from one location to another.…”
Section: Six Reasons Why the Mr Big Technique Is Inherently Flawedmentioning
confidence: 99%